Spatiotemporal characterization of zonal flows with multi-channel correlation Doppler reflectometers in the HL-2A Tokamak. (4th September 2015) - Zhong, W.L.; Shi, Z.B.; Xu, Y.; Zou, X.L.; Duan, X.R.; Chen, W.; Jiang, M.; Yang, Z.C.; Zhang, B.Y.; Shi, P.W.; Liu, Z.T.; Xu, M.; et al.
Abstract: The oscillations of poloidal plasma flows induced by radially sheared zonal flows are investigated by newly developed correlation Doppler reflectometers in the HL-2A tokamak. The non-disturbing diagnostic allows one to routinely measure the rotation velocity of turbulence, and hence the radial electric field fluctuations. With correlation Doppler reflectometers, a three-dimensional spatial structure of geodesic acoustic mode (GAM) is surveyed, including the symmetric feature of poloidal and toroidal E r fluctuations, the dependence of GAM frequency on radial temperature and the radial propagation of GAMs. The co-existence of low-frequency zonal flow and GAM is presented. The temporal behaviors of GAM during ramp-up experiments of plasma current and electron density are studied, which reveal the underlying damping mechanisms for the GAM oscillation level.